The Structure of Dental Plaque Microbial Communities in the Transition from Health to Dental Caries and Periodontal Disease. Issue 16 (26th July 2019) - Valm, Alex M.
Abstract: The human oral cavity harbors diverse communities of microbes that live as biofilms: highly ordered, surface-associated assemblages of microbes embedded in an extracellular matrix. Oral microbial communities contribute to human health by fine-tuning immune responses and reducing dietary nitrate. Dental caries and periodontal disease are together the most prevalent microbially mediated human diseases worldwide. Both of these oral diseases are known to be caused not by the introduction of exogenous pathogens to the oral environment, but rather by a homeostasis breakdown that leads to changes in the structure of the microbial communities present in states of health. Both dental caries and periodontal disease are mediated by synergistic interactions within communities, and both diseases are further driven by specific host inputs: diet and behavior in the case of dental caries and immune system interactions in the case of periodontal disease. Changes in community structure (taxonomic identity and abundance) are well documented during the transition from health to disease. In this review, changes in biofilm physical structure during the transition from oral health to disease and the concomitant relationship between structure and community function will be emphasized. Graphical Abstract: Unlabelled Image Highlights: Dental caries and periodontal disease are the most prevalent microbially mediated diseases that afflict humans. Dental plaque has a highly ordered structure mediated by intercellular interactions, and environmental and host inputs. Periodontal disease is associated with shifts in microbial community structure, that is, taxonomic membership and abundance. Periodontal disease is thought to be mediated by synergist interactions between subgingival microbial communities and host. Spatial structure of intact supragingival and subgingival biofilms is equally important as taxonomic composition for understanding microbiome changes in health and disease.